Feature Papers in Food Chemistry - Nardini, Mirella (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint collects high-quality manuscripts with a focus on food composition, with special emphasis on chemical characterization, the content of bioactive molecules, contaminants, and analytical aspects. The roles of variety, cultivation, growing conditions, and technological processes on the nutritional quality of foods have been investigated. Studies dealing with the biological activity and health benefits of bioactive food molecules have been also considered.